Microbial network-driven remediation of saline-alkali soils by salt-tolerant plants - Cui, Yushuang; Ning, Zhifang; Li, Menglu; Qin, Xue; Yue, Xin; Chen, Xiaobo; Zhu, Changxiong; Sun, Hongyong; Huang, Yali (Frontiers in Microbiology, 2025)
Salt-tolerant plants (STPs) play an important role in saline-alkali soil remediation, but their interaction with soil microorganisms remain incompletely elucidated. This study explored the effects on microbial community structure, function, and soil quality in saline-alkali land of four treatments: no plant (CK), Triticum aestivum L. (TA), Tamarix chinensis Lour. (TC), and Hibiscus moscheutos Linn. (HM). The results indicated that the planting of TC, TA, and HM effectively reduced soil electrical conductivity (EC) by 82.9, 88.3, and 86.2%, respectively. TC and TA significantly decreased the pH from 8.79 to 8.35 and 8.06, respectively, (p < 0.05). Moreover, the nutrient content and enzymatic activities were enhanced. Notably, TA exhibited the most significant soil nutrient improvement. STPs also substantially altered the microbial community structure and function, with TC increasing bacterial richness (ACE and Chao1 indices) compared to other treatments (p < 0.05). Moreover, TA significantly promoted the relative abundance of unclassified_Gemmatimonadaceae, unclassified_Vicinamibacterales, and Mortierella (p < 0.05). A major innovation of this study is using network analysis to explore microbial interactions, revealing how STPs enhance microbial network complexity. This approach identified Sphingomonas as a key taxon in TA soils, shedding light on the microbial dynamics of soil remediation. Additionally, partial least squares path model (PLS-PM) showed that soil quality improvements were primarily driven by shifts in bacterial composition, offering a novel mechanistic framework for understanding microbial contributions to soil restoration. This research advances the understanding of microbial-plant interactions and underscores the innovative application of network analysis in phytoremediation, offering valuable insights for future soil restoration strategies.